MONITORING OF THE ELDERLY CHOLESTEROL LEVELS OF SUMBERSONO VILLAGE, MOJOKERTO REGENCY, EAST JAVA PROVINCE, INDONESIA - Endah Prayekti; Ary Andini (UNUSA Press, 2021)
Parties who become partners in community service activities are the village community of Sumbersono, Mojokerto Regency. Based on the 2017 health profile in Mojokerto District, there are 117,309 elderly people. The Mojokerto district government has a health program for the elderly, namely the Elderly Health Service (Usila). Usila is a health service according to the standards in the elderly guidelines in a health facility in one work area and time period. Examination of the elderly programmed by the Mojokerto district government has been carried out at the Puskesmas that serves the elderly, but the elderly need more routine checks to monitor cholesterol levels. Another thing that is a problem is the relatively expensive cholesterol examination so that there are limitations in the self-examination by the community. Cholesterol examination methods for community service were using POCT and interviews related to health complaints from community service participants. There were 44 community service participants, not only from the elderly but from middle age. Of the 27 elderly, 10 elderly have normal cholesterol levels while 17 elderly have high and very high of cholesterol levels. Of the 17 middle age participants, 7 of them had normal cholesterol levels and 10 people had high and very high cholesterol levels. The interviews showed that almost all participants had health complaints that resembled complaints due to high cholesterol level. It is recommended to perform other health examination and not be limited to the elderly.